2019
DOI: 10.1177/1749602019879856
|View full text |Cite
|
Sign up to set email alerts
|

From ‘secret’ online teen drama to international cult phenomenon: The global expansion of SKAM and its public service mission

Abstract: This article addresses the production, distribution and global expansion of the online teen drama, SKAM/SHAME (2015–2017), produced by the Norwegian public service broadcaster NRK. The article combines perspectives on transmedia storytelling with production studies and studies of public service broadcasting to investigate the distinct production, publishing and promotion models underpinning SKAM, as well as its public service mission. Furthermore, it addresses SKAM’s transition from a ‘secret’ online teen dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 34 publications
1
49
0
4
Order By: Relevance
“…Skam has been studied from various perspectives, giving priority to literary theory, media theory and social science (see Lindtner et al 2018;Krüger et al 2019;Sundet 2020). The role of religion in the fourth season has been examined, where Sana, a Muslim girl, is the main character (Aarvik 2018).…”
Section: The Skam Seriesmentioning
confidence: 99%
“…Skam has been studied from various perspectives, giving priority to literary theory, media theory and social science (see Lindtner et al 2018;Krüger et al 2019;Sundet 2020). The role of religion in the fourth season has been examined, where Sana, a Muslim girl, is the main character (Aarvik 2018).…”
Section: The Skam Seriesmentioning
confidence: 99%
“…Although several studies have addressed the convergence of television, journalism and/or politics with social media (e.g. Agger andMortensen 2016, Enjolras et al 2013;Enli and Skogerbø 2013;Kalsnes 2016;Larsson and Moe 2014;Sundet 2018), there is a gap in the research literature on the hybrid of social media and Norwegian film industry. In addition, there is currently no published Nordic research addressing how the film industry utilizes social media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instagram was central in the show’s distribution and several of the main characters had their own Instagram accounts that were integral to the story. Skam is also an illuminating example of how media texts spread through networked cultures and went from being a ‘secret Norwegian online teen drama to an international phenomenon’ (Sundet, 2020) and of a thriving and supportive online culture (Krüger and Rustad, 2019). A few examples: in 2018, it was reported that the series has been downloaded 180 million times on Chinese Weibo (Max, 2018).…”
Section: Introductionmentioning
confidence: 99%